The effect of Ochratoxin A and its biodegradation secondary products in zebrafish embryos (Danio Rerio) - Garai, Edina; Kerekes, Flóra; Urbányi, Béla; Cserháti, Mátyás; Márton, Dalma; Csenki, Zsolt (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
Nowdays, contaminated areas size by mycotoxins have been growing. Based on recent studies, all the Aspergillus species have been found in all Hungarian regions. Many methods are known for the detoxification of mycotoxins. One of them is biodegradation which was also used in our experiments. During the microbial biodegradation of mycotoxins, in some cases secondary products might be more toxic than the original mycotoxins are. According to the EFSA statement, metabolites from mycotoxins’ degradation processes need to be also examined. During our former works we applied the method of microinjection for toxicity analyses. This method was used to certify the microbial strain OTA-degrading ability. During microinjection, predetermined amounts of test materials were injected into the embryos. At 120 hpf, embryos’ lethal endpoint was examined. During classification of bacterial strain we tested normal, toxin-free control containing only the metabolic products of the microorganisms, and degraded samples from the strain. The bacterial strain showed 96% degradation efficiency in our experiments. The outcomes were compared with the results of 5 ppm OTA. Based on our results, ŐR 16 bacterial strain (Cupriavidus Basilensis) produces toxic materials but they are less poisonous than OTA is. The degradation secondary products are also showed a lower toxicity than OTA did. The conclusion is that ŐR 16 bacterial strain suitable to use for the detoxification of OTA-contaminated feed in confined places.
Keywords: ochratoxin A; zebrafish; microinjection; biodegradation